Uji Stabilitas Kombinasi Gel Lidah Buaya (Aloe vera (L.) Webb) dan Madu dengan Menggunakan 2 Basis Na-CMC Berbeda: Stability Test of Combination of Aloe Vera (Aloe vera (L.) Webb) and Honey Gel Using 2 Different Na-CMC Bases - Rifki Ilmy Fahlevi; Adam M. Ramadhan; Fika Aryati (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Aloe vera (L.) Webb and honey have been used medicinally in several cultures for thousands of years to have antibacterial and anti-inflammatory properties. Gel dosage formulations can be done with several types of ingredients by taking into account the selection of the gelling agent used. This study aims to determine the stability of a gel preparation made from the active combination of aloe vera extract and honey with 2 different Na CMC bases, namely 5 grams (F1) and 2.5 grams (F2). Aloe vera is extracted by maceration method and then made into a gel preparation according to the predetermined formulation. The combination gel formulation of aloe vera extract and honey was evaluated based on organoleptic test, viscosity test, preparation pH, homogeneity, and dispersibility. The results showed that the homogeneity and pH of the preparations were in accordance with the specified criteria, but the viscosity and spreadability tests did not meet the specified criteria. The organoleptic results of the two formulas have a yellowish brown color, a slightly pungent odor and a slightly sticky texture. It was concluded that the best gel in the dosage formulation used in this study was a gel based on 5 grams of Na CMC (F1).